Pengaruh Pengungkapan Corporate Social Responsibility terhadap Nilai Perusahaan pada Indeks Saham LQ45 - Gusfarini Fauziah; Abdul Kohar Irwanto; Muhammad Syamsun (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2016)
CSR disclosure in Indonesia were still low and voluntary. CSR disclosure is expected to increase positive image of the company and attract investors to invest. This study aims: (1) analyze the effect of CSR disclosure toward corporate financial performance of LQ45 stock index (2) analyze the effect of CSR disclosure toward corporate stock performance of LQ45 stock index and (3) analyze the effect of financial performance toward corporate stock performance of LQ45 stock index. This study used the annual report and financial report of the sample companies on 2013. Test of relationship influences of CSR disclosure toward corporate value were measured by Structural Equation Modelling (SEM). The results of this study showed valid indicators as a measurement construct of CSR disclosure in the LQ45 stock index were environment and society but economic, Human Rights (HAM), social and product responsibility indicators were invalid. Valid indicators of financial performance as a measurement constructs were ROA but DER, DAR, NPM, and ROE were invalid. While PBV was valid as a measure of stock performance construct but EPS were invalid. The results of hypothesis testing explained CSR disclosure were not significant effect on the finansial performance and had negatively related. CSR disclosure were not significant effect on the stock performance and had negatively related. However financial performance were significant effect on the stock performance and had positively related.